Toxicity study on Clinacanthus nutans leaf hexane fraction using Danio rerio embryos - Murugesu, Suganya; Khatib, Alfi; Ahmed, Qamar Uddin; Ibrahim, Zalikha; Uzir, Bisha Fathamah; Benchoula, Khaled; Nik Yusoff, Nik Mohd. Idris; Perumal, Vikneswari; Alajmi, Mohamed Fahad; Salamah, Sahal; El-Seedi, Hesham (Elsevier, 2019)
Clinacanthus nutans, an herbal shrub belonging to the Acanthaceae family, is traditionally used as a functional food to treat various ailments in Malaysia and Indonesia. Although the polar fraction of this plant shows nontoxic effect, the toxicity of the non-polar extract is not reported so far. The present study aimed to assess the toxic effect and determine the lethal concentration of this non-polar fraction using zebrafish embryos. The n-hexane fraction was partitioned from the crude extract of C. nutans obtained using 80% methanolic solution. After spawning of the adult male and female zebrafish, the eggs were collected, transferred into a 96-well plate and incubated with the n-hexane fraction at concentrations of 15.63 μg/ml, 31.25 μg/ml, 62.5 μg/ml, 125 μg/ml, 250 μg/ml and 500 μg/ml in 2% DMSO. The survival and sublethal endpoint were assessed, the mortality and hatchability rates were calculated based on microscopic observation, while the heartbeat rate was measured using DanioScope software. The median lethal concentration (LC50) of the C. nutans n-hexane fraction, which was determined using probit analysis, was calculated to be 75.49 μg/mL, which is harmful. Moreover, gas chromatography-mass spectrometry (GC–MS) analysis revealed the presence of palmitic acid, phytol, hexadecanoic acid, 1-monopalmitin, stigmast-5-ene, pentadecanoic acid, heptadecanoic acid, 1-linolenoylglycerol and stigmasterol in the n-hexane fraction.